Reducing the Use of Imprisonment: lessons from 20 years’ experience in Canada - Reid, Andrew A. (The British journal of criminology, 2020)
In order to reduce or constrain prison populations, many different strategies have been proposed, trialled, or implemented. In 1996, Canada created the first and, to date, most ambitious home confinement sanction, the Conditional Sentence of Imprisonment (CSI). This study tracks annual changes to correctional admissions since the introduction of the sanction to assess whether it has reduced custodial admissions for Aboriginal offenders. There is evidence that the CSI had a modest decarceration effect overall and for Aboriginal offenders specifically. These effects were strongest in the initial years after the sanction was introduced, with waning performance in the most recent decade. The decarceration effects have not been erased but nor has the serious problem of over-incarceration among Aboriginal offenders.